Variations In Body Composition Among Adult Males With Different Lifestyles - Aklamati, E.K. (University of Ghana, 2001)
Knowledge about body composition is essential when one considers nutritional status, body weight, and health. Excess body fat is associated with chronic diseases such as diabetes mellitus, coronary heart diseases and strokes, while underweight or under-nutrition in adults can result in reduced work capacity and affect productivity. Both conditions exist in developing countries. Research on body composition is widespread in developed countries. Literature is, however, not readily available on the trends in body composition in developing countries. This study was carried out with the aim of investigating trends in body composition among adult males and how they are influenced by age, socio-economic status (measured by the mean grade point system), energy expenditure, energy intake, and energy balance. Information on age, socio-economic status, energy expenditure, and energy intake were obtained using questionnaires, while anthropometric measurements were taken using standardized procedures. Measures of body composition were derived using various equations from which Upper-arm Fat Estimate (UFE), Fatmass (FM), Total Skinfold Thickness (TSKF), Percent Body Fat (BF%der and BF% l e a n ), Body Mass Index (BMI) and Waist-Hip Ratio (WHR) were used as indicators of body fat, while Lean Tissue Mass (LTM) and Bone Mineral Content (BMC) were used as indicators o f fat-free mass. The mean age o f the study population was 35.4 years. From regression analysis, age was found to be a significant determinant of both fat mass and fat-free mass. Ten men were found to have accumulated abdominal fat (WHR > 0.98), and the minimum age for this group was 42 years. Socio-economic status was also found to be a significant predictor for all the indicators o f body composition. Construction workers had the highest mean energy expenditures (4005 kcal/day), and the lowest mean energy intakes (3432 kcal/day). On the contrary, office workers had the lowest mean energy expenditure and the highest mean energy intake. Construction workers also had the least values for mean FM, LTM, and BMC (8.45 kg, 51.67 kg and 3.94 kg, respectively). Office workers had the highest mean FM (11.61 kg), while drivers had the highest values for LTM and BMC (53.52 kg, and 5.01 kg, respectively). Men who were in the low socio-economic group had the smallest energy balance (-134.3 kcal), with those in the high socio-economic group having the highest (positive) energy balance (1346 kcal). Energy expenditure, energy intake, and energy balance were significant determinants for UFE and TSKF, while their influence in predicting FM, BF%der, BF%lean, LTM, and BMC were not significant — 0 .0 0 ). Age and socio-economic status were significantly related to all indicators o f body composition. Occupation had a marked effect on energy intake and energy expenditure, and also on FM, LTM, and BMC. The expected result between energy expenditure and energy intake and some indicators were not seen and this could have been due to reliance on the memory of the respondents for information as they might have over- or under-estimated their energy intake and expenditure
Thesis (MPhil) - University of Ghana, 2001